2021
DOI: 10.9734/jpri/2021/v33i33a31772
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes and their Phenomenal Possibilities in the Treatment of Various Neurodegenerative Disorders: An Overview

Abstract: At present, research in the field of the brain does not cease to surprise us with new facts and discoveries that no one could have suspected about 30 years ago. But it was at the time when it became clear that the cerebral neurons are not the only cells that can respond to changes in the external environment. A real scientific boom began to study a heterogeneous group called glia. And scientists are paying close attention to the largest of them – astrocytes. Understanding the importance of astrocytes in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It was found that the activity of N-acetyltransferase (NAT -N-acetyltransferase) decreases during pregnancy. In some cases, caffeine was used to show that the normal activity of Nacetyltransferase in healthy women decreases during pregnancy [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the activity of N-acetyltransferase (NAT -N-acetyltransferase) decreases during pregnancy. In some cases, caffeine was used to show that the normal activity of Nacetyltransferase in healthy women decreases during pregnancy [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of literary and statistical data gives the right to assert that there are no finished products for people of older age groups that correspond to the physiological norms of consumption of basic macro-and micronutrients. In this regard, in order to systematize scientific approaches to meeting the needs of older age groups in basic energy substances, the results of research have been analyzed [4][5][6][7][8][9][10]. It has been established that the optimal, from a scientific point of view, the ratio between the main substances (%) is -proteins: fats : carbohydrates -(16-20) : (25-30) : (55-59).…”
Section: Resultsmentioning
confidence: 99%
“…They determine the importance of the geriatric problem, the negative consequences of which provoke degenerative diseases of the heart, blood vessels, kidneys, digestive organs, musculoskeletal system, including joints and the like [3][4][5][6][7]. Axiomatic is the fact that it is advisable to influence the nature, pace and direction of such changes in metabolism, adaptive and compensatory processes by rationally providing optimal nutrition that will meet the specific needs of natural aging [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Gluten sensitivity without celiac disease is another exciting concept. Some patients with irritable bowel syndrome and functional dyspepsia who do not have signs of gluten disease experience a significant improvement in symptoms after excluding gluten from their diet [15,16]. Basic principles of treatment of functional disorder of the gastrointestinal tract in anxiety disorders are showed in Table 1.…”
Section: The Role Of Dietmentioning
confidence: 99%